1975
DOI: 10.1177/000348947508400612
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Failures in Cancer of the Larynx

Abstract: Overwhelming statistics have been published regarding the success of radiation therapy in the management of laryngeal carcinoma. The fate of those patients whose cancers are not controlled by radiotherapy is often left to speculation. An analysis is made of 61 patients with early and advanced laryngeal cancer treated initially with radiation therapy and subsequently operated upon because of recurrent or persistent tumor. Frequently, diagnosis of recurrence is difficult or delayed. Preservation of voice can onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Kirchner 29 emphasized that if initial curative laryngeal RT for squamous cell carcinoma was unsuccessful, islands of tumor remained throughout the field, resulting in a wide area of recurrence. Various authors have also reported that vertical partial laryngectomy after RT failure for glottic carcinoma should not be attempted if 1. the true vocal cord was immobile, 2. the arytenoid cartilage or its mucosa were directly involved by tumor, 3. the tumor involved more than one third of the opposite true vocal cord, 4. there was either evidence of perichondritis or thyroid cartilage invasion, and 5. transglottic spread of disease was noted 1‐15 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kirchner 29 emphasized that if initial curative laryngeal RT for squamous cell carcinoma was unsuccessful, islands of tumor remained throughout the field, resulting in a wide area of recurrence. Various authors have also reported that vertical partial laryngectomy after RT failure for glottic carcinoma should not be attempted if 1. the true vocal cord was immobile, 2. the arytenoid cartilage or its mucosa were directly involved by tumor, 3. the tumor involved more than one third of the opposite true vocal cord, 4. there was either evidence of perichondritis or thyroid cartilage invasion, and 5. transglottic spread of disease was noted 1‐15 …”
Section: Discussionmentioning
confidence: 99%
“…The exact site involved by recurrent tumor is presented in Table I. According to the reported selection criteria, 1‐15 contraindications for salvage vertical partial laryngectomy (VPL) in the patients with glottic tumor included fixation of the true vocal cord (3 patients), transglottic extent of disease (1 patient), anterior infraglottic extent of disease (4 patients), invasion of more than one third of the contralateral true vocal cord (2 patients), invasion of the anterior aspect of the ipsilateral arytenoid cartilage (3 patients), and recurrent tumor exceeding its original limits (9 patients). Similarly, 13 horizontal partial laryngectomy was not indicated due to anterior commissure invasion, posterior vestibule invasion, and recurrent tumor exceeding its original limits in all 3 patients with supraglottic tumor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fistula formation seems to be part of a prognostically unfavourable picture. Of the 12 Pharyngocutuneous Jistulae '9 Group I (23) Fistulae (7) No fistulae (16) It may be mentioned that all of the fistulae closed spontaneously without surgical treatment. Bresson ct ul.…”
Section: Discussionmentioning
confidence: 99%
“…All this often leads to late discovery of the recurrence, leaving many patients who are eligible for surgical salvage needing to undergo total laryngectomy. 15,34 Som 35 was the first to publish results on CLS as salvage therapy after RT in 1951. More recently, Ganly and colleagues 28 noted that local control rates for salvage total laryngectomy were 65% to 85% for T1 and T2 glottic tumors, whereas local control rates for salvage CLS range from 66% to 96%.…”
Section: Introductionmentioning
confidence: 99%